2017
DOI: 10.1146/annurev-neuro-072116-031312
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Cellular and Molecular Mechanisms for Magnetosensation

Abstract: Diverse animals ranging from worms and insects to birds and turtles perf orm impressive journeys using the magnetic field of the earth as a cue. Although major cellular and molecular mechanisms for sensing mechanical and chemical cues have been elucidated over the past three decades, the mechanisms that animals use to sense magnetic fields remain largely mysterious. Here we survey progress on the search for magnetosensory neurons and magnetosensitive molecules important for animal behaviors. Emphasis is placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Magnetotactic bacteria (MTB) biomineralize intracellular, membrane-bounded, nano-sized magnetic mineral crystals of magnetite (Fe 3 O 4 ) and/or greigite (Fe 3 S 4 ) called magnetosomes and are characterized by their ability to sense and swim along Earth’s magnetic field lines [ 3 ]. Magnetosomes are the only magnetoreceptors definitively located at a specific site within cells so far and are a sufficiently well-characterized system with which the origin and evolution of magnetotaxis can be explored [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotactic bacteria (MTB) biomineralize intracellular, membrane-bounded, nano-sized magnetic mineral crystals of magnetite (Fe 3 O 4 ) and/or greigite (Fe 3 S 4 ) called magnetosomes and are characterized by their ability to sense and swim along Earth’s magnetic field lines [ 3 ]. Magnetosomes are the only magnetoreceptors definitively located at a specific site within cells so far and are a sufficiently well-characterized system with which the origin and evolution of magnetotaxis can be explored [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence that magnetoreception is widespread in the animal kingdom, a magnetoreceptor and accompanying underlying neural circuitry have yet to be identified in any animal (Shaw et al, 2015;Clites and Pierce, 2017;Nordmann et al, 2017). Many reasons have been cited for why magnetoreceptors have proven elusive, including the absence of large, obvious magnetoreceptive organs and the possibility that magnetoreceptors could exist anywhere within an animal (Johnsen and Lohmann, 2005;Shaw et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that animals and birds that migrate can use magnetic field detection systems in their brains, as well as optic sensing to direct navigation during migration (reviewed in [23]). It has also been reported that exposure to weak magnetic fields can manipulate regeneration in worms either positively or negatively depending on the field strength [24].…”
Section: Space Flight-the New Opportunity For Understanding Homo Sapiensmentioning
confidence: 99%